Crossword puzzles' effect on third-grade students' cognitive abilities in energy learning - Tia Rahmania; Supriansyah Supriansyah (Inovasi Kurikulum, 2025)
Cognitive ability plays a vital role in supporting student success at the elementary level. However, observations at SDN Kedaung Kaliangke 01 Pagi, West Jakarta, revealed that learning is still predominantly dominated by conventional media, making lessons less engaging and resulting in lower cognitive outcomes. This study aimed to examine the effect of Crossword Puzzle media on the cognitive abilities of third-grade students. A quasi-experimental method with a Nonequivalent Control Group Design was used. The sample consisted of 60 students divided into two groups: the experimental group received instruction using Crossword Puzzle media, while the control group received conventional teaching. The instrument was a multiple-choice test that had been validated for both validity and reliability. Data analysis included normality and homogeneity tests, followed by hypothesis testing using an Independent Sample t-test and effect size. The results showed a significant difference in cognitive abilities between the two groups. The experimental group demonstrated better conceptual understanding and more active engagement. These findings indicate that Crossword Puzzle media effectively enhances memory, concentration, analytical skills, and thinking ability. Therefore, this media is recommended as an innovative alternative to improve cognitive skills, especially in elementary science lessons on energy topics.   Abstrak Kemampuan kognitif memiliki peran krusial dalam menunjang keberhasilan belajar peserta didik di jenjang sekolah dasar. Namun, hasil observasi di SDN Kedaung Kaliangke 01 Pagi, Jakarta Barat, menunjukkan bahwa proses pembelajaran masih didominasi oleh media konvensional, sehingga cenderung kurang menarik dan berdampak pada rendahnya capaian kognitif peserta didik. Berdasarkan permasalahan tersebut, penelitian ini bertujuan untuk mengetahui pengaruh media Crossword Puzzle terhadap kemampuan kognitif peserta didik kelas III SD. Metode yang digunakan adalah kuasi eksperimen dengan desain Nonequivalent Control Group Design. Sampel terdiri atas 60 peserta didik yang dibagi ke dalam dua kelompok, yaitu kelompok eksperimen yang menggunakan media Crossword Puzzle dan kelompok kontrol yang mengikuti pembelajaran konvensional. Instrumen berupa tes pilihan ganda yang telah diuji validitas dan reliabilitasnya. Analisis data dilakukan melalui uji normalitas, homogenitas, serta uji hipotesis menggunakan Independent Sample t-Test dan effect size. Hasil penelitian menunjukkan perbedaan yang signifikan pada kemampuan kognitif antara kedua kelompok. Kelompok eksperimen menunjukkan pemahaman konsep yang lebih baik dan keterlibatan aktif dalam pembelajaran. Temuan ini membuktikan bahwa Crossword Puzzle efektif dalam meningkatkan daya ingat, konsentrasi, kemampuan analitis, dan berpikir peserta didik. Oleh sebab itu, media ini direkomendasikan sebagai alternatif inovatif untuk meningkatkan kemampuan kognitif peserta didik, khususnya dalam pembelajaran IPAS pada topik energi. Kata Kunci: kemampuan kognitif; pembelajaran energi; sekolah dasar; teka-teki silang